Effect Of Overbrengen Delay From CY To CFS Warehouse On Stripping Implementation At PT. Internusa Hasta Buana - Wani Sihaloho, Otri (International Journal of Science, Technology & Management, 2023)
In goods import activities at PT. Internusa Hasta Buana overloaded from the Container Yard (CY) to the CFS Warehouse. Delays in ships and Delivery Order documents are factors that cause overbregan delays and will affect stripping productivity at PT Internusa Hasta Buana. The aim of this research is to analyze the effect of overbregan delays on stripping productivity at PT Internusa Hasta Buana. Data collection techniques using observation and interviews. The population of this research is container handling activities at PT. Internusa Hasta Buana with samples namely Overbringing and Stripping Activities which experienced delays at PT. Internusa Hasta Buana Jakarta, in 2007. The method used is quantitative description. The results of the research show the results of the analysis regarding the relationship between late Overbringing and Stripping at PT. Internusa Hasta Buana using correlation analysis shows a value of r = 0.83. This proves that the influence of Overbrengen delay on Stripping has a strong and positive relationship on the productivity of PT's Stripping implementation. Internusa Hasta Buana, the results of hypothesis testing with an error rate of 5% on all sample data, obtained the number t0 = 4.36 > t table = 1.182 so that Ho: r = 0 is rejected and Ha: r> 0 is accepted, meaning there is a significant relationship between Delay Overbrengen and implementation of Stripping at PT CFS Warehouse. Internusa Hasta Buana and the results of the analysis of the influence of Overbrengen delays on the implementation of Striping using coefficient analysis obtained the regression equation model Y = 9.17 + 1.01, which means that if the variable for Overbrengen and stripping delays (X) increases by 9.17 times then the variable for the number of containers which in Overbrengen and Stripping will increase by 1.01 times. The results of the determining coefficient obtained were 68%, meaning that the influence of late Overbrengen on the implementation of Stripping at the CFS Warehouse of PT. Internusa Hasta Buana was 68% and the remaining 32% was due to other factors being ignored, as well as delays in Overbringing to PT's CFS warehouse. Inernusa Hasta Buana is caused by several factors including: delays in Delivery Order documents from shipping companies.